A Review of the Research and Development of High-Frequency Measurement Technologies Used for Nonlinear Dynamics of Drillstring - Lixin Li; Jin Wang; Yingmei Yu; Yifei Xing; Fengyan Zhang; Yi Zhang; Yanyan Li (Shock and Vibration)
High-frequency measurements can provide much more new insights for drillstring dynamics compared to traditional instruments, leading to a new realm of understanding of drillstring behaviors in great detail than before. In this paper, data acquisition tools with high-frequency sample rates and the data processing are introduced. Based on high-frequency data, progress of drilling dynamics is summarized, including new understandings of low-frequency drillstring dynamics, high-frequency torsional oscillations (HFTOs), and high-frequency axial oscillations (HFAOs) and new findings for the coupling of vibrations and motions, as well as models and simulation methods to deeply comprehend high-frequency dynamics of drillstring. High-frequency measurements have been used for enabling drillers to improve drill performance, especially for field decision making, BHA selection, and bit design, usually through the ways of minimizing vibrations to obtain high-efficient drilling conditions, the high-frequency response near bit can also be used for lithology identification during drilling. Though there still exists a gap between research perspective and drilling practice, the industry of high-frequency measurements has gotten off a good start, which has huge potential to avoid nonproductive time thereupon reducing drilling cost in the future.